Mapping Knowledge Of Gymnastics Nifas, Stomach Tapel And Massage In Mother Nifas - Alfi Laili; Musdalina; Ruri Aditya Sari (Science Midwifery, 2021)
Maternity care period is an urgent transition period for mother's, babies and their family physiologically, socially and emotionally. The condition caused pain and death of mothers and baby risks commonly within maternity care in this period. The objective of this study is to discover the knowledge of Tapel, postpartum exercise and massage oxytocin used during postpartum. The population of this study is married woman who has got babies in Langkat, Deli Serdang and Medan. They are 74 women. The sample was taken by purposive sampling method. The data was collected by addressing questionnaire about Tapel, postpartum exercise and massage oxytocin knowledge such as definition, understanding the benefits, the way to use and the functions. The lowest knowledge about it was respondents with education Senior high school 66.7%, calling mothers (34, 6%) and they aree 30-34 years old (34.8%). Furthermore, women who knows the way to treat Tapel correctly 54.1%. Postgraduate respondents within age 35-39 years old shows the sufficient knowledge about postpartum exercise (50%). This finding shows that it is very important to do an action to improve itin order to avoid abuse that impact pain so hard.